Iron Oxides : from nature to applications - Faivre, Damien (Wiley-VCH Verlag GmbH & Co. KGaA, 2016)
This handbook and ready reference covers all important aspects of the information available on iron oxides. A preliminary overview chapter discusses iron oxide minerals with their unique structures and properties, before the following section goes on to deal with the formation and transformation of iron oxides, covering geological, synthetic, medical, and microbiological as well as physico-chemical aspects. A chapter on corrosion from a chemical engineering viewpoint completes this section. Subsequent chapters are devoted to characterization techniques. Besides such classical methods as IR/Raman and MOssbauer spectroscopy, special attention is focused on X-ray based techniques, magnetic measurements, and electron microscopy for structural characterization. The final section is mainly devoted to exciting new applications of magnetic iron oxides, for example, in medicine. Additional chapters on geo/paleomagnetism, environmental aspects, and pigments illustrate the full scope of applications. A must-read for anyone working in the field.- Resumé vydavatel
Keywords: oxidy; železo; oxides; iron; oxid železa; elektronické knihy; monografie; electronic books; monographs